Detection of intrapartum fetal hypoxia using admission test (AT) - Gurung, Geeta; Rana, Ashma; Giri, Kanti (Nepal Journal of Obstetrics and Gynaecology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objective: The purpose of the present study is to find out the effectiveness of admission test (AT) in detecting fetal hypoxia in labour and to correlate the results of AT with perinatal outcome. Methods: This was a prospective study, conducted in the department of Ob/Gyn, TU, Teaching Hospital. A total of 100 women in labour were selected for the study. All of them were subjected to Admission test which is 15-20 minutes recording of fetal heart rate and uterine contractions on cardiotocograph machine at the time of admission in labour. The result of AT were not revealed to concerned Obstetrician in labour room and the labouring women and the results of the test were evaluated after delivery so that the clinical management is not changed according to the AT result. Result: The results of AT were: Reactive in 73%, Equivocal in 23% and Ominous in 4%. Women with reactive AT had low risk of developing intraapartum fetal distress (1%) as compared to 4.3% of equivocal and 50% of ominous group. Operative delivery for fetal distress was required in only 1.4% of reactive group in comparison to 4.3% of equivocal and 50% of ominous group. Resuscitation was required in 1.4% of reactive group, 8.7% of equivocal and 25% of ominous group. Four babies required neonatal unit and NICU admission for neonatal sepsis (2 from reactive, 2 from equivocal group) and none suffered from intranatal hypoxia. Conclusion: The AT seems to be useful to detect fetal distress already present at admission and seems to have some predictive value for fetal well being for the next few hours of labour. Key words: Admission test, Cardiotocograph, fetal heart rate, fetal distress, fetal hypoxia, perinatal outcome. doi:10.3126/njog.v1i2.1487 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 10 - 13 Nov-Dec 2006